Simulation-Based Basic Life Support and Choking Training for High School Students - Jansen Fernando; Rachmadina Rachmadina; Marni Sianturi; Soraya Soraya; Nugraha Putra (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This study aimed to improve the knowledge and skills of 12th-grade students in Basic Life Support (BLS) and choking management through simulation-based health education at SMA Negeri 6 Pekanbaru. Research Methodology: A one-group pre-test–post-test community service design was conducted on 80 students using interactive lectures, group discussions, live demonstrations, and hands-on practice with BLS and choking manikins; knowledge questionnaires and skill checklists adapted from the 2020 American Heart Association guidelines were used for evaluation. Results: The mean knowledge score increased from approximately 60 (pre-test) to 90 (post-test), and most participants shifted from unskilled to skilled categories in recognizing cardiac arrest, performing chest compressions with adequate depth and rate, and applying the correct choking-relief sequence. Conclusions: Simulation-based health education effectively enhanced high school students’ basic life support and choking management competencies and has the potential to strengthen emergency preparedness within the school environment. Limitations: This study used a single-group design in one school without long-term follow-up; therefore, causal inference and skill retention over time could not be fully assessed. Contributions: The program provides a practical model for integrating simulation-based BLS and choking training into school health promotion activities and offers guidance for educators, public health practitioners, and policymakers seeking to build community first-responder capacity among adolescents.